Persepsi Masyarakat Mengenai Obat Tradisional di Kelurahan Simpang Baru Kecamatan Tampan Kota Pekanbaru - RATNA SARI DEWI (Jurnal Penelitian Farmasi Indonesia, 2019)
Traditional medicine is medicine that is used empirically for traditional medical derived from plants, animals, minerals, preparations (galenic), or a mixture of these materials that can be made into various dosage forms including capsules, tablets, pills and others, without using medicinal chemicals. This study aims to determine public perceptions about traditional medicine in the Simpang Baru Village, Tampan District, Pekanbaru City. This research is an observational / survey research which is descriptive in nature. Sampling was done by purposive sampling, the sample obtained in this study were 105 respondents who had used traditional medicine the last three months. The results showed that there was still a good public perception of traditional medicine in Simpang Baru Village. From these results it can be concluded that the perceptions that arise in the community regarding traditional medicine are traditional medicines made in Indonesia, the content is safer (halal) (87.8%) and for the perception of the reasons people use traditional medicines because traditional medicines are hereditary (82.7%).